Тhe study of Association of gene polymorphism with sports success and risk of alimentary-dependent diseases in athletes representing cyclic sports - E. Yu. Sorokina; E. E. Keshabyants; N. N. Denisova (National Electronic Information Consortium (NEICON), 2020)
The studies of genetic polymorphisms rs1815739 (ACTN3 gene), rs2016520 (gene PPARD), rs1042713 (ADRB2 gene), rs1799945 (HFE gene), rs1801282 (PPARG gene) of athletes involved in cyclic sports were carried out. Genotyping was performed using allele-specific amplification with real-time detection of results and the use of TaqMan probes. As a result of the research, a higher incidence of alleles associated with endurance (T-polymorphism rs1815739 and G - polymorphism rs2016520) was revealed in athletes of cyclic sports. The analysis of the results of genetic polymorphisms: rs9939609 gene FTO, ADRB3 rs4994 gene rs2228570 and VDR gene showed that the risk of development of alimentary-related diseases (obesity and osteoporosis) in the examined athletes after sports career is lower than in the General population.